Stochastic Characteristics of De- Noising Time Series - Ali, Amira Desouky Ibrahim (المجلة العلمية للدراسات و البحوث المالية و التجارية : علمية محكمة., 2023)
Astrophysical, geophysical, meteorological, and other types of physical data can be the result of an experiment, emerge as a signal from a dynamical system, or include sociological, economic, or biological data. it is always assumed that a certain level of noise will be present in time series data, regardless of its source. the analysis of all such data in the presence of noise frequently produces inaccurate results. the time series data filtering technique is a tool to remove as many of these bugs as we can and simply prepare the data for additional analysis. when you filter a time series, you keep some frequencies while removing the spectral strength at others. both time series analysis and digital signal processing (DSP) make extensive use of filters in applications for DSP. here, we tried to create an adjustable method of filtering a time series with the idea that the series had performed the necessary de-noising and modification updates. these qualities were determined in this study. we've proven analytically that the current model can effectively resist errors and preserve positional significance in the time series. when such data are analyzed in a noisy environment, the results are frequently misinterpreted. so, before we can begin the extensive investigation, we must first build an initial platform by de-identifying the data. it is usually necessary to deal with the problem of filtering a time series of data. in this work, we analysis the Fourier series with respect to the finite Fourier transform, resulting in the determination of the properties of this series. the outcomes of this study improve understanding of this series' characteristics. يمكن أن تكون البيانات الفيزيائية الفلكية والجيوفيزيائية والأرصاد الجوية وأنواع أخرى من البيانات الفيزيائية تظهر نتيجة لتجربة معينة، أو تظهر كإشارة من نظام ديناميكي في شكل سلسلة زمنية. من المفترض دائما وجود مستوى معين من الضوضاء في بيانات هذه السلاسل الزمنية، بغض النظر عن مصدرها. غالبا ما ينتج عن تحليل جميع هذه البيانات في وجود ضوضاء نتائج غير دقيقة. تعد تقنية تصفية بيانات السلاسل الزمنية من الضوضاء أداة لإزالة أكبر عدد ممكن من هذه الأخطاء، عندما تقوم بتصفية أو بإزالة الضوضاء من سلسلة زمنية، فإنك تحتفظ ببعض الترددات بينما تزيل القوة الطيفية في أخرى. يستخدم كل من تحليل السلاسل الزمنية ومعالجة الإشارات الرقمية (DSP) بشكل مكثف المرشحات في تطبيقات (DSP)، حاولنا هنا إنشاء طريقة معدلة لتصفية سلسلة زمنية من الضوضاء مع فكرة أن السلسلة قد أجرت التحديثات اللازمة لإزالة الضوضاء والتعديل. تم تحديد هذه التعديلات في هذه الدراسة. لقد أثبتنا بشكل تحليلي أن النموذج الحالي يمكن أن يقاوم الأخطاء بفاعلية ويحافظ على الأهمية الموضعية في السلسلة الزمنية. عندما يتم تحليل هذه البيانات في بيئة مليئة بالضوضاء أو الأخطاء كثيرا ما تكون النتائج غير دقيقة. لذلك، قبل أن نتمكن من بدء الدراسة الشاملة، يجب علينا أولا إنشاء تحليل أولى عن طريق تحديد البيانات المراد تنقيتها أو تصفيتها. عادة ما يكون من الضروري التعامل مع مشكلة تصفية سلسلة زمنية من البيانات. في هذا العمل، قمنا بتحليل سلسلة فورييه المحدود، مما أدى إلى تحديد خصائص هذه السلسلة نتائج هذه الدراسة تحسن فهم خصائص سلسلة فورييه المحدود.